Human subthalamic nucleus neurons differentially encode speech and limb movement - Johari, Karim; Kelley, Ryan M.; Tjaden, Kris; Patterson, Charity G.; Rohl, Andrea H.; Berger, Joel I.; Corcos, Daniel M.; Greenlee, Jeremy D. W. (Frontiers in Human Neuroscience, 2023)
Deep brain stimulation (DBS) of the subthalamic nucleus (STN), which consistently improves limb motor functions, shows mixed effects on speech functions in Parkinson’s disease (PD). One possible explanation for this discrepancy is that STN neurons may differentially encode speech and limb movement. However, this hypothesis has not yet been tested. We examined how STN is modulated by limb movement and speech by recording 69 single- and multi-unit neuronal clusters in 12 intraoperative PD patients. Our findings indicated: (1) diverse patterns of modulation in neuronal firing rates in STN for speech and limb movement; (2) a higher number of STN neurons were modulated by speech vs. limb movement; (3) an overall increase in neuronal firing rates for speech vs. limb movement; and (4) participants with longer disease duration had higher firing rates. These data provide new insights into the role of STN neurons in speech and limb movement.